Study Of STEM-Based Learning Against 4C Skills (Critical, Creative, Communication, and Collaboration) In Science - Novianti, Baiq Aryani; Nitiasih, Putu Kerti; Riastini, Putu Nanci (Jurnal Ilmiah Profesi Pendidikan, 2023)
The development of the 21st century is the rapid development of science, technology, and information affecting almost every single aspect of life, one of which is education. The educational element is required to produce graduates with quality and competitiveness to withstand the demands of skills needed in the 21st century. In the era of the 21st century, 4C skills are critical for every student, one of which is through STEM-based Learning in the subject of science. The article purposely examines how STEM-based Learning forms 4C skills in science subjects. A library research approach uses a descriptive qualitative method to collect intended data. The result shows that implementing a STEM approach to 4C skills in science subjects can be performed in Indonesia to prepare competent human resources to deal with the challenges of the 21st century, such as building cognitive abilities, manipulation, designing, utilizing technology, and knowledge practice.